The Role of Financial Technology on the Nexus Between Demographic, Socio-economic, and Psychological Factors, and the Financial Literacy Gap - Samira Ben Belgacem; Ghousia Khatoon; Hussaini Bala; Abad Alzuman (SAGE Open)
The increased accessibility and adoption of FinTech in emerging economies prompts researchers to investigate its moderating impact on the prevalent determinants of financial literacy. This research investigates the influence of demographic, socio-economic, psychological, and FinTech innovation factors on mitigating the financial literacy gap. Structured questionnaires were used to obtain primary data from the 1,100 Saudi potential participants. The descriptive and inferential statistics were computed using the Statistical Package for Social Sciences. The study findings revealed that FinTech innovation as a moderating variable has a limited impact on closing the financial literacy gap. Besides, marital status, income, spouse’s educational background, as well as psychographic characteristics like “present financial situation,”“meet monthly payments,”“future is hopeless,” and “don’t expect change” have a bearing on the financial literacy gap. Additionally, women lacked confidence when responding to queries on financial literacy. Finally, the study concludes with implications for the policy-making bodies.